ANALISIS BIAYA MODAL TERHADAP TINGKAT PENGEMBALIAN INVESTASI PADA PT. HARIMUGABE JAYA - Hasan, A. Yaniarsyah (Jurnal Ilmiah Widya, 2013)
Cost of capital is very important for a company in their business especially to analyze cost of capital to the rate of investment’s return. The higher the investor’s demands for the share, the higher the share’s price. The objective of this study is to find out weather the cost of capital’s analysis relevant to determine share’s rate of the return and the minimum of cost of capital can obtain the maximum share’s rate of return. The study was condacted at Harimugabe Jaya enterprice located in Jakarta. The method used field survey and analyzed descriptively and exploratively. The result indicates that the cost of capital’s analysis is relevant to determine the share’s rate of the return and the minimum of cost of capital can obtain the maximum share’s rate of return. Harimugabe Jaya enterprice which using capital’s source fully from loan can reduce the cost of capital become 20,14 % which is previously equal to 34,12 %.